2016
DOI: 10.37546/jaltsig.pie5.1-1
|View full text |Cite
|
Sign up to set email alerts
|

Drama in the L2 Classroom: A Defense and Practicum

Abstract: A case is made for the use and practice of drama and dramatic activities in order to engage students in the second language (L2) classroom. This article also attempts to clarify terms such as drama, theatre, and dramatic activities within a second language classroom context. In order to make the case for drama in the L2 classroom, well-established trends in contemporary pedagogy are presented. Coupled with Maley & Duff’s benefits of drama in the L2 classroom, the overall intent of this article is to empowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Numerous studies have shown that theatre and drama can have beneficial foreign language learning effects (Carson, 2012;Dodson, 2002;Horghagen & Josephsson, 2010;Ryan-Scheutz & Colangelo, 2004). These benefits can be seen in terms of the improvement of specific language skills as well as motivation (Barbee, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies have shown that theatre and drama can have beneficial foreign language learning effects (Carson, 2012;Dodson, 2002;Horghagen & Josephsson, 2010;Ryan-Scheutz & Colangelo, 2004). These benefits can be seen in terms of the improvement of specific language skills as well as motivation (Barbee, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dramatic activities are any activities that engage students in both drama and theatre. Within the context of the language classroom, the benefits of both drama and theatre coincide with the basic concepts of several holistic methods of language teaching including Communicative Language Teaching (CLT), Task-based Learning (TBL), and Total Physical Response (TPR) (Barbee, 2016;Davies, 1990). Nina Spada (2007) states that CLT validates drama as pedagogy in the language classroom, writing that CLT is "a meaning-based, learner-centered approach to L2 teaching where fluency is given priority over accuracy and the emphasis is on the comprehension and production of messages" (p. 272).…”
Section: Dramatic Activities In the Classroommentioning
confidence: 99%
“…Dramatic activities in the classroom can include but are not limited to mime, simulation, role-playing, improvisation, teacher-in-role, playwriting, and various types of theatre performances from monologues and scenes to readers theatre and full productions (Barbee, 2016;Davies, 1990).…”
Section: Dramatic Activities In the Classroommentioning
confidence: 99%
See 1 more Smart Citation
“…Through execution of the changes, I am going to make based on educational research, I anticipate that students' speaking anxiety will be alleviated to a large extent. It will directly result in their linguistic and emotional development, thus boost their frequency and confidence in English speaking [4] .…”
Section: Introductionmentioning
confidence: 99%